Using Connected Technologies in a Continuous Quality Improvement Approach in after-school Settings: The PAX Good Behavior Game. Issue 4 (2nd October 2019) - Cava-Tadik, Yasemin; Phillips Smith, Emilie; Yu, Dian; Leathers, Megan; Farris, Jaelyn R.
Abstract: This demonstration study explored the use of connected technologies in a continuous quality improvement (CQI) approach to implementing evidence-based practices in after-school. Focus group with staff indicated enjoyment of technology and offered feedback for future development. Ecological momentary assessments (EMA) were gathered daily. Three randomized conditions were compared among 4 programs and 12 staff implementing PAX Good Behavior Game (PAX GBG). Analysis of variance (ANOVA), Post-Hoc Tukey, and chi-square analyses indicated that the tech-enhanced condition showed better implementation using scoreboards than the in person, while similar in game length. Both were superior to the control in behavioral strategies; highlighting the promise of technology in capacity building.